(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
In this article, the issues that are important in determining the priorities of the reform of higher education in our country, raising the moral, moral and intellectual development of the young generation to a new level in terms of quality are taken into account. Also, recommendations and opinions on the formation and development of universal competence in the higher education system were analyzed within the framework of the world standard.